Effect of oxytocin and misoprostol in the induction of labor in pregnant women at term with premature rupture of membranes in regional Hospital Honorio Delgado. - Lidia Cespedes de Covinos (2019)
A main problem during treatment of pregnant patients with premature rupture of membranes is that the need induction of labor that can be initiated with either oxytocin or misoprostol . Currently, there is no consensus in literature about the best treatment for inducing labor with a minimum risk for both mother and babyThe objective of this study was to compare the efficacy and complications of intravaginal misoprostol compared with oxytocin. The objective of this study was to compare the efficacy and complications of intravaginal misoprostol with oxytocin for labor induction in patients with premature rupture of membranes.It was a prospective, longitudinal, comparative, experimental study performed in the Department of Obstetrics at the Honorio Delgado Espinoza Regional Hospital in Arequipa from January to December2010.52 pregnant patients were randomized in two groups. 26 patients were given 0.25 mg misoprostol and 26 received Oxytocin perfusion for labor induction. Clinical evolution of these patients was followed in pre labor, labor, and post labor.There was no statistically significant difference in duration of latent phase, active phase, duration of fetal delivery, placental delivery fetal suffering , type of labor termination and Apgar at I or 5 minutes. There were significant differences for complications during expulsive period, the rates for postpartum hemorrhage , uterine hypotonia, and prolonged expulsive period were higher in misoprostol group while for oxytocin the most frequent complication was placental retention.Our conclusion was that for labor induction the duration of dilation, expulsion, termination of labor and Apgar of baby is similar in patients given misoprostol and oxytocin, but use of oxytocin showed less complications than misoprostol